The Sendratasik Student Working Group Orchestra as an Initiative of the Sendratasik Education Study Program in Achieving Key Performance Indicators (KPIs) - Sugito, Tomy; Handayaningrum, Warih; Karoso, Subianto; Hardinanto, Eko (Proceeding of International Joint Conference on UNESA, 2025)
This research will describe and examine the efforts of the Sendratasik Education study program, especially in obtaining achievements in the non-academic field after the course reshuffle where the loss of major courses (elective principal instruments) for students who take the entry path through the discipline of music. In some decades to achieve in the non-academic field is not something easy. It requires a good, organized, measured process in participating in the competition scene and accuracy in combining non-academic competition stalks at regional, national and international levels. Sendratasik education is expected to be able to bring its academic community in a direction that can support the vision and mission. As part of a university that produces qualified cultural arts teachers, it is necessary to achieve directed and measurable performance. The measure of quality in the credibility of the institution is measured by the accreditation component with seven standards (now nine standards). One of the standards that support Unesa's main performance indicators is through achievement. The achievement is in two parts, namely academic and non-academic achievement. As a foothold in this study using the theory of achievement and the process to achieve success as a theory used to dissect the achievement of key performance indicators, especially in non-academic achievement in the Sendratasik Education Study Program, Faculty of Languages and Arts, Surabaya State University. This research uses a mix method research method. with an achievement process approach in the Sendratasik Study Program. The data sources taken are primary and secondary data. Data includes questionnaires, writings, interviews, documentation, and observations then use achievement process analysis contained in leadership management to review the standardization that has been determined by the accreditation agency.